Continuing education for the public secondary school library personnel in the Division of Quezon City needs assessment - Bautista, Elizabeth S. (1984)
The study assessed the continuing education needs of the secondary school library personnel in the Division of City School, Quezon City. Specifically, it aimed to identify the library personnel's actual job activities, their perceived continuing education needs and preferred continuing education modes and course content.